2022
DOI: 10.1108/ijrdm-09-2021-0394
|View full text |Cite
|
Sign up to set email alerts
|

Impulse buying behaviour in omnichannel retail: an approach through the stimulus-organism-response theory

Abstract: PurposeThis study investigates impulse buying as a consumer behaviour outcome in omnichannel retail through the stimulus-organism-response (S-O-R) theory. For such, the authors addressed convenience and channel integration as the stimuli, the relationship among consumer empowerment, trust, satisfaction, and perceived value as the organism, and impulse buying as the response.Design/methodology/approachAn online survey was conducted with 229 customers of a Brazilian retailer that adopts the omnichannel strategy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 72 publications
(243 reference statements)
1
37
0
Order By: Relevance
“…However, no research has determined these behaviors driven by the dimensions of ISSQ developed by Zhang et al (2022), emphasizing the quality attributes of the channel-integrated physical store (which differs from a conventional brick-and-mortar store), which is addressed in our current study. Focusing our discussion on recent omnichannel literature, researchers have demonstrated that dimensions of online and offline channel integration have a positive impact on omnichannel shoppers’ impulse purchase behavior (Pereira et al , 2021), value co-creation like citizenship behavior (Natarajan and Veera Raghavan, 2023a), their stickiness intentions with store (Lin et al , 2022b) and subsequent patronage intentions (Lim et al , 2022). Researchers have also gone a step ahead to demonstrate how omnichannel capability impacts customer satisfaction through their sense of empowerment (Ürgüplü and Yumurtacı Hüseyinoğlu, 2021), subsequently, how patronage intentions are formed out of customer empowerment and satisfaction (Mishra et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, no research has determined these behaviors driven by the dimensions of ISSQ developed by Zhang et al (2022), emphasizing the quality attributes of the channel-integrated physical store (which differs from a conventional brick-and-mortar store), which is addressed in our current study. Focusing our discussion on recent omnichannel literature, researchers have demonstrated that dimensions of online and offline channel integration have a positive impact on omnichannel shoppers’ impulse purchase behavior (Pereira et al , 2021), value co-creation like citizenship behavior (Natarajan and Veera Raghavan, 2023a), their stickiness intentions with store (Lin et al , 2022b) and subsequent patronage intentions (Lim et al , 2022). Researchers have also gone a step ahead to demonstrate how omnichannel capability impacts customer satisfaction through their sense of empowerment (Ürgüplü and Yumurtacı Hüseyinoğlu, 2021), subsequently, how patronage intentions are formed out of customer empowerment and satisfaction (Mishra et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Focusing our discussion concerning omnichannel retail literature, researchers in the past have relied upon this framework to model the stimuluses like channel integration quality (Gao and Huang, 2021;Hamouda, 2019;Lee et al, 2019;Pereira et al, 2022), omnichannel capability ( € Urg€ upl€ u and Yumurtacı H€ useyino glu, 2021), perceived channel integration (Cheah et al, 2022;Lim et al, 2022;Zhang et al, 2018) and perceived channel agility (Son et al, 2021). The impact of these stimulus(S) variables on internal customer states (O) like consumer empowerment (Zhang et al, 2018), trust (Lim et al, 2022;Lin et al, 2022), satisfaction (Hamouda, 2019;Lim et al, 2022), perceived value (Hamouda, 2019), customer engagement (Gao and Huang, 2021;Lee et al, 2019) and relationship program effectiveness (Gao and Huang, 2021) were studied in detail.…”
Section: Bopis User's Citizenship Behaviormentioning
confidence: 99%
“…The impact of these stimulus(S) variables on internal customer states (O) like consumer empowerment (Zhang et al, 2018), trust (Lim et al, 2022;Lin et al, 2022), satisfaction (Hamouda, 2019;Lim et al, 2022), perceived value (Hamouda, 2019), customer engagement (Gao and Huang, 2021;Lee et al, 2019) and relationship program effectiveness (Gao and Huang, 2021) were studied in detail. With regard to the response (R) variables, customer loyalty (Gao and Huang, 2021;Hamouda, 2019), satisfaction ( € Urg€ upl€ u and Yumurtacı H€ useyino glu, 2021), patronage intentions (Lim et al, 2022), purchase intentions (Zhang et al, 2018), repurchase intentions (Lee et al, 2019), impulse buying behavior (Pereira et al, 2022) and intention to spread positive word-of-mouth (Lee et al, 2019) have been studied extensively using this framework.…”
Section: Bopis User's Citizenship Behaviormentioning
confidence: 99%
“…(2023) work, where they used a qualitative exploratory design with in-depth interviews of Generation Z customers and retail firms were used to provide insights into the dynamic capabilities necessary for obtaining omnichannel retailing. Pereira et al . (2023) explored impulse buying as a consumer behaviour outcome in omnichannel retail through the stimulus-organism-response theory.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Recent literature includes Solem et al (2023) work, where they used a qualitative exploratory design with in-depth interviews of Generation Z customers and retail firms were used to provide insights into the dynamic capabilities necessary for obtaining omnichannel retailing. Pereira et al (2023) explored impulse buying as a consumer behaviour outcome in omnichannel retail through the stimulus-organism-response theory. In addition, Li et al (2023) developed a stylised model to explore omnichannel coupon promotion strategies considering consumers' time sensitivity in redeeming coupons.…”
Section: Introductionmentioning
confidence: 99%